Oesophageal Perforation Treated Non-Operatively in an HIV/AIDS Positive Patient: A Case Report (Tanzania Medical Journal, 2009)
Oesophageal perforation is a rare condition that causes significant morbidity and may be fatal. A successful outcome is obtained by prompt recognition of the diagnosis, aggressive resuscitation and institution of conservative measures, before rushing for specific surgical intervention. Oesophageal stricture is one of the complications which occurin HIV/AIDS patients due to oesophageal candidiasis, cytomegalovirus and herpes zoster lesions. The treatment is conservative and consists of dilatation endoscopically; the procedure also carries a risk of perforation or tear at the stricture site. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 37-38